2006
DOI: 10.1111/j.1365-2524.2006.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Home-based palliative care in Sydney, Australia: the carer's perspective on the provision of informal care

Abstract: The provision of home-based palliative care requires a substantial unpaid contribution from family and friends (i.e. informal care). The present cross-sectional descriptive study, conducted between September 2003 and April 2004, describes this contribution and the impact it has on those providing informal care. The participants were 82 informal carers of patients registered with two community palliative care services in Sydney, Australia (40% of eligible carers). Carers were interviewed to assess the care reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(110 citation statements)
references
References 29 publications
4
103
0
2
Order By: Relevance
“…Views are maintained over five years since caring at a constant rate. The most surprising aspect of these findings is the factors that are not predictive of future unwillingness to caredbeing the spouse of the deceased (given some of the other associations that have been noted in the literature 24 ), the person's diagnosis, 9,24,35e37 perceived levels of unmet needs (despite evidence that caregivers with depression have increased levels of unmet needs 37 and there are specific tasks they would prefer not to undertake 8 ), and the use of specialist palliative care services. 30 …”
Section: Key Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Views are maintained over five years since caring at a constant rate. The most surprising aspect of these findings is the factors that are not predictive of future unwillingness to caredbeing the spouse of the deceased (given some of the other associations that have been noted in the literature 24 ), the person's diagnosis, 9,24,35e37 perceived levels of unmet needs (despite evidence that caregivers with depression have increased levels of unmet needs 37 and there are specific tasks they would prefer not to undertake 8 ), and the use of specialist palliative care services. 30 …”
Section: Key Resultsmentioning
confidence: 96%
“…8 In end-of-life care, the role of caregiver is often a subtle transition of growing involvement in increasingly complex care. 9,10 Having a caregiver is still the single most important predictor of home death 11e14 where this is agreed between patient and caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…Research describes both carers' and patients' risk-factors and the 'optimal' kind of services required to support caregivers and people with terminal illnesses when they are cared for at home (Foreman, Hunt, Luke & Roder, 2006;Hudson, 2003;Palliative Care Australia, 2005;Tang, 2003;Zapart, Kenny, Hall, Servis & Wiley, 2007). The consequences for carers of providing EoLC include adverse physical, social and psychological effects with stress, poor mental health, sleep disruption, fatigue, family and social isolation all noted as significant burdens (Grande et al, 2009;Zapart et al, 2007). The physical and psychological demands of the caring role itself can lead to adverse health and social outcomes for carers; the Australian Institute of Health and Welfare (2008) reported that older carers were more likely than their non-carer peers to have a disability (61% to 51%) and although a third felt satisfied with their caring role, a similar proportion frequently felt fatigue and weariness.…”
Section: The Nature Of Caringmentioning
confidence: 99%
“…Only one study had been carried out in the UK, 223 with three carried out in the US, [224][225][226] one in Canada, 227 one in Australia 228 and one in Finland. 229 In the main, the studies were of mixed groups of demented and physically frail older people; however, two studies focused on people with mild dementia, 224,226 one of which involved African American carers only, 226 and two studies examined palliative care.…”
Section: Update Of Systematic Review For Period December 2005-april 2008mentioning
confidence: 99%
“…229 In the main, the studies were of mixed groups of demented and physically frail older people; however, two studies focused on people with mild dementia, 224,226 one of which involved African American carers only, 226 and two studies examined palliative care. 223,228 The two studies of palliative care were concerned with carer needs and identified respite as one of the main needs, along with information and support. Respite at home was the most commonly requested.…”
Section: Update Of Systematic Review For Period December 2005-april 2008mentioning
confidence: 99%